The Socio-Historical Study of Interfaith Harmony Forum (FKUB) and Its Contribution to the Creation of Religious Harmony in Kediri - Subakir, Ahmad (Journal of Islamic Studies and Civilization, 2025)
This study explores the socio-historical development of the Interfaith Harmony Forum (Forum Kerukunan Umat Beragama/FKUB) and its contribution to sustaining religious harmony in Kediri City, East Java. Kediri, historically a multicultural hub since the Airlangga Kingdom (11th century) and later shaped by Hindu-Buddhist traditions, Dutch colonial missions, and Islamic boarding-school culture, remains one of Indonesia’s most tolerant cities. Using a qualitative descriptive-analytical approach, the article examines how FKUB—founded in 1998 as a response to the May 1998 riots—together with the Paguyuban Antar Umat Beragama dan Penghayat Kepercayaan (PAUB/PKUB), the Faculty of Ushuluddin of IAIN Kediri (now UIN Syekh Wasil Kediri), and the youth-focused Paguyuban Lintas Masyarakat (PaLM), has mediated interfaith tensions, promoted dialogue, and organized inclusive social programs. The findings reveal that these institutions have significantly reduced religious conflict, strengthened social cohesion, and enhanced Kediri’s Harmony Index—reaching 3.91 in 2019 and keeping the city among Indonesia’s top-ten most tolerant. The study highlights that historical inclusivity, continuous dialogue, youth engagement, and state-community collaboration are key to sustaining religious moderation and offer a transferable model for other plural societies.